Koustrup –En middelalderlig torp i Vestjylland - Henningsen, Helle (Kuml, 2002)
Koustrup A medieval thorp in Western Jutland In the mid-1980s, a farmer ploughed up stones and clay on some fields adjoining an old road in an area known as Koustrup in the parish of Velling near Ringkøbing (fig. 1). Following this, amateur archaeologists investigated the area and located five medieval farm sites. Four farm sites were on the southern side and one was on the northern side of an east-west running road, which may go back to the Middle Ages. Some of the farm sites were visible on aerial photos (fig. 2). The farms were built on a moor in the early Middle Ages, and the settlement was probably inhabited until the 14th century. Ringkøbing Museum investigated the westernmost farm site in 1992 without recovering definite house remains. The second farm site from the East was excavated in the summers of 1994 to 1996.This paper presents the results of these in vestigations. The area to be excavated was divided into two large areas, I and II. A dwelling house and its surroundings were excavated in area I (fig. 3), and the remains of farm buildings and other structures in area II. The dwelling house first appeared as an oblong clay area: the clay floor (fig. 4). Along the edges of this floor, some large stones appeared. They were arranged in a row, and although some were missing, it was clearly the remains of a sill. In the middle of the northern row of sill stones there was a bay-like projection (fig. 5). There were only a few post holes in the house, and although some were following the axis of the house, the house did not seem to have had central roof-carrying posts. More likely, the walls were carrying the roof. Some postholes aligned across the house towards each end may indicate partition walls that divided the house into a large middle room and two smaller gable rooms. The gables were difficult to distinguish, but two oval pits containing stones may be the remains of the western gable (fig. 6), whereas a very deep posthole towards the south-east marked one corner of the eastern gable. The oldest fireplace in the house was a pit, which may have had a wooden superstructure, perhaps a spark-catcher (fig. 7). Along the inside of the northern wall east of the projection were the remains of an oven, which had had a mud-built vault. This oven belongs to the latest phase of the house. There were also traces of a couple of fireplaces on the clay floor. Postholes outside the house indicate a couple of light wooden buildings close to the dwelling house. Traces of another oven were found at the middle of the southern house wall. In the eastern end of the house was a 3-m long stone-lined pit (fig. 8), which is interpreted as a low cellar. Two stone-paved areas were excavated at the east end of the house. They may be connected with entrances in the eastern gable. The majority of the finds from the dwelling house are potsherds of the local brown/grey, coarsely tempered ware also known from the oldest layers of Ringkøbing (fig. 9). The numerous rimsherds with flanged rims indicate that the clay vessels are mainly of the gloular type (fig. 10). The rimsherds could be divided into three main groups: A, with a curved flanged rim (fig. 11); B, with a rim bent outward in an almost right angle (fig. 12); and C, with a pronounced bend between the neck and the rim and a wide rim meant to support a lid (fig. 13). Apart from sherds from globular vessels, there were sherds of unglazed jugs, dishes, and bowls (fig. 14). Only a few sherds from glazed jugs were found, one with a twisted handle (fig. 15). Other artifacts from the dwelling house were whetstones made from Norwegian micaschist (fig. 16) and some rusty iron objects, mainly nails and spikes. The dwelling house remains in area I are well preserved, although marked by cultivation in modern times. The house had a width of 5.5 meters and a length of 18 meters. Charcoal from the cooking pit and from a waste layer outside the projection were C14-dated. The result shows that the house was in use in the decades around 1250. Together with the artifacts, this point s at the 13th century as the function period. The knowledge of medieval country houses in Western Jutland is sparse, as it is limited to just a few finds. The dwelling house of an excavated medieval farm by Fjand also had a row of sill stones, but in this case, the sill was supporting massive turf walls, and the roof was supported by central roof-carrying posts. Turf walls in combination with central roof-bearing posts were common in areas with sparse timber. However, in Koustrup there was enough timber available for building, and the walls were probably half-timbered and fixed in a sill beam resting on the sill stones. The small projection in the north wall is unusual in the Danish material. Area II was situated south east of area I. It was laid out in order to locate the farm buildings of the medieval farm. Aerial photos showed faint house silhouettes in th is place. However, very little was preserved (fig. 17). The northern part of the area was characterized by a large peat layer, which had been filled into a 60- cm deep hole dug into the hill from the east – perhaps a store for house building, or for bedding in the stables. Later, a small peat-wall building with an oven (C, fig. 1 8) was erected on top of the layer. The surface had traces of two more fireplaces: A, by the western edge of the area, and B, some four meters from the western edge. In and around these structures were several medieval potsherds (fig. 19). South of the large peat blotch were the traces from a building running north-south. Unfortunately, only traces of the western wall were found, but enough of this was left for three building phases to be established. The older phase was represented by a row of postholes, which could be followed for 15 meters. The southernmost 9.5 meters consisted of six pairs of double posts. When the building was altered, these walls were replaced by peat walls resting in foundation trenches. When these walls were later replaced, new foundation trenches were dug into the old ones. However, this time stones were placed in the ditches before the peatwalls were erected on top (fig. 24). In the middle of the long wall was an interval without stones, perhaps indicating a door. Area II did not provide as much pottery as area I. Some sherds from globular vessels with the rim forms A, B, and C were collected, but just a single glazed sherd. A quern stone of garnet micaschist originates from Norway (fig. 21). Several rusty iron items were found in the area, mainly nails.The most interesting single find was a small Romanesque bronze cross (fig. 22). It was found using a metal detector and measures 3.6 x 2.8 cm. The weight is 7 g. The cross is from c. 1200 and has an ornamentation of engraved lines with traces of gilt. A missing cross arm may indicate that the cross was broken off a casket or other item. Although there were no instantly recognizable house sites, we have established medieval activity in area II. Whether the structural remains are from the farm’s stables and barns, or the remains of an older croft settlement is unknown. Aerial photos and investigation of the two areas showed trenches and ditches that may have been part of the demarcation of the medieval croft (fig. 24). A ditch running along the northern side of the dwelling house in area I may indicate the northern end of the croft. In area II, the structural remains were cut by two succeeding north-south running ditches, the assumed eastern end of the croft. Southernmost in area II was a large peat-filled ditch running east-west, which may indicate the southern perimeter (fig. 23). The early Middle Ages were times of prosperity for North-western Europe, and so the populations grew. New land was put under the plough, and many left their villages in order to found new settlements, the so-called thorps. In Denmark, around 4000 localities with the name ending ”- torp ” or the derivatives ” -tarp ”, or ”-trup ” are known. Around half of these belong to existing settlements, such as Koustrup. This name was supposedly created from the personal name of ”Kok” and ”torp”. The village was first mentioned as ”Coxtrup” in a written source from the mid-15th century. After the good times of the many thorp foundations, Denmark suffered a drastic recession in the first half of the 14th century. Civil wars and crop failure was followed by the plague, and many thorps and farms were deserted. Perhaps the Koustrup settlement was given up at that time. At least the area was uninhabited then, but new investigation has shown that Koustrup was revived in the late Middle Ages some two hundred meters to the south of the 13th century settlement. Some of the farms in this ”new” Koustrup were mentioned in late medieval sources,and three of the farms still exist (fig. 25). The excavations in Koustrup have increased our knowledge of the country settlement in Western Jutland in the late Middle Ages. Many questions have been answered, and new ones have been asked. It is a fascinating thought that the inhabitants of the first Koustrup may have witnessed both the erection of the Veiling Church and so me hundred years later the sprouting up of the market town of Ringkøbing. Helle Henningsen Ringkøbing Museum Translated by Annette Lerche Trolle